PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN PAPAN PERKALIAN UNTUK MENINGKATKAN KEMAMPUAN PERKALIAN SISWA KELAS III - Aliya Ningsi Lasimpala; Rifda Mardian Arif; Andi Marshanawiah; Nur Sakinah Aries; Hadi Yamin Assel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem formulation in this study was: “Can the multiplication calculation skills of third-grade students at SDN 56 Kota Timur be improved through the implementation of the Problem-Based Learning model assisted by multiplication board media?” This study aimed to improve students’ multiplication calculation skills through the application of a Problem-Based Learning (PBL) model supported by multiplication board media among third-grade students at SDN 56 Kota Timur. The research employed a Classroom Action Research (CAR) design. The findings involving 19 students indicated that in Cycle I, 11 students achieved the learning mastery criteria, representing 58% of the total participants. This result had not yet met the predetermined performance indicator target of 80%; therefore, the study was continued to Cycle II. In Cycle II, 16 students successfully achieved the learning mastery criteria, accounting for 84% of the participants, thereby fulfilling the established performance indicator target. Based on the results and discussion conducted in each cycle, it can be concluded that the implementation of the Problem-Based Learning model assisted by multiplication board media was effective in improving the multiplication calculation skills of third-grade students at SDN 56 Kota Timur.